Gastroprotective Efficacy of Coenzyme Q10 in Indomethacin-Induced Gastropathy: Other Potential Mechanisms. (6th February 2012) - Malash, Asmaa M.; Agha, Azza M.; Kenawy, Sanna A.; Abdallah, Dalaal M.
Abstract : Tough recently the mitochondrial bioenergetic coenzyme (Co)Q10 has been shown to protect against indomethacin-induced gastric ulceration, yet the full mechanistic cassettes have not been investigated. Therefore, the current investigation assessed further gastroprotective mechanisms of CoQ10 using the indomethacin-induced gastropathy model. While CoQ10 was administered at 3 dose levels to male Wistar rats, the proton pump inhibitor, pantoprazole, was given at 4 dose levels ahead of pyloric ligation and indomethacin administration. Indomethacin evoked gastric ulcerations that were associated by decreased gastric mucosal nitric oxide and glutathione levels. The NSAID reduced gastric volume and mucin content, but increased titratable acidity, acid output, and peptic activity. CoQ10, especially at the higher dose levels, as well as pantoprazole pretreatments reverted almost all diversions induced by the NSAID to different extends. Moreover, preadministration with the nonselective nitric oxide synthase inhibitor, L-NAME, boosted ulcer formation that was associated by suppression of gastric mucosal nitric oxide in CoQ10 and pantoprazole-treated groups. The current investigation shows that CoQ10 guards against gastric ulceration via its partial inhibition of titratable acidity and peptic activity, as well as enhancement of mucin secretion due to both gastric mucosal nitric oxide and glutathione replenishment, especially at the higher dose levels.